Dysregulated mTOR networks in experimental sporadic Alzheimer’s disease - de la Monte, Suzanne M.; Tong, Ming (Frontiers in Cellular Neuroscience, 2024)
Background: Beyond the signature amyloid-beta plaques and neurofibrillary tangles, Alzheimer's disease (AD) has been shown to exhibit dysregulated metabolic signaling through insulin and insulin-like growth factor (IGF) networks that crosstalk with the mechanistic target of rapamycin (mTOR). Its broad impact on brain structure and function suggests that mTOR is likely an important therapeutic target for AD. Objective: This study characterizes temporal lobe (TL) mTOR signaling abnormalities in a rat model of sporadic AD neurodegeneration. Methods: Long Evans rats were given intracerebroventricular injections of streptozotocin (ic-STZ) or saline (control), and 4 weeks later, they were administered neurobehavioral tests followed by terminal harvesting of the TLs for histopathological study and measurement of AD biomarkers, neuroinflammatory/oxidative stress markers, and total and phosphorylated insulin/IGF-1-Akt-mTOR pathway signaling molecules. Results: Rats treated with ic-STZ exhibited significantly impaired performance on Rotarod (RR) and Morris Water Maze (MWM) tests, brain atrophy, TL and hippocampal neuronal and white matter degeneration, and elevated TL pTau, AβPP, Aβ, AChE, 4-HNE, and GAPDH and reduced ubiquitin, IL-2, IL-6, and IFN-γ immunoreactivities. In addition, ic-STZ reduced TL pY1135/1136 -IGF-1R, Akt, PTEN, pS380 -PTEN, pS2448 -mTOR, p70S6K, pT412 -p70S6K, p/T-pT412 -p70S6K, p/T-Rictor, and p/T-Raptor. Conclusions: Experimental ic-STZ-induced sporadic AD-type neurodegeneration with neurobehavioral dysfunctions associated with inhibition of mTOR signaling networks linked to energy metabolism, plasticity, and white matter integrity.